EFL Students’ Difficulties in Writing Thesis - Ayu Oktaviani; Citra Raflesia; Yulfi Yulfi (Linguistic, English Education and Art (LEEA) Journal, 2024)
The objective of this research was to investigate EFL students’ difficulties in writing their thesis. This research used qualitative approach. The English Education Study Program of UNPARI students which still doing a thesis took part in this research as subject of the research. The data were collected by asking the students to fill out the questionnaires and being interviewed afterward. In analyzing data, it was done by checking the students’ answer in the questionnaire, classifying the students’ answers, describing the data and concluding the results. The result showed that there were several internal factors of EFL students’ difficulties in writing a thesis. In internal factors are difficulty in choosing the title of the thesis, feel are not sure (pessimistic), bored or saturated, doubtful or pessimistic, fears or worries, having a health problem or down while working on the thesis. Other factors are students' ability in understanding the systematics of writing the thesis, tending to use translation tools, lack og grammar and vocabulary, spelling, and punctuation in writing the thesis correctly. While, external factors were having communication problems with supervisors and supervisors’ writing, have difficulty in finding references related to thesis titles in the internet, there are no complete reference sources and no free access to digital libraries on campus, having technical problems on devices, have financial problems, personal problems, surrounding environment is not/less conducive. The researchers hope the result of this research will become important considerations for lecturers in advising their students especially in writing their thesis. Keywords: Difficulties, EFL Students, Thesis, Writing